Midwives being ‘with woman’: An integrative review - Bradfield, Zoe; Duggan, Ravani; Hauck, Yvonne; Kelly, Michelle (Elsevier BV, 2017)
Background Midwives being ‘with woman’ is embedded in professional philosophy, standards of practice and partnerships with women. In light of the centrality of being ‘with woman’ to the profession of midwifery, it is timely to review the literature to gain a contemporary understanding of this phenomenon. Aim This review synthesises research and theoretical literature to report on what is known and published about being ‘with woman’. Methods A five step framework for conducting an integrative literature reviews was employed. A comprehensive search strategy was utilised that incorporated exploration in electronic databases CINAHL, Scopus, Proquest, Science Direct and Pubmed. The initial search resulted in the retrieval of 2057 publications which were reduced to 32 through a systematic process. Findings The outcome of the review revealed three global themes and corresponding subthemes that encompassed ‘with woman’: (1) philosophy, incorporated two subthemes relating to midwifery philosophy and philosophy and models of care; (2) relationship, that included the relationship with women and the relationship with partners; and (3) practice, that captured midwifery presence, care across the childbirth continuum and practice that empowers women. Conclusion Research and theoretical sources support the concept that being ‘with woman’ is a fundamental construct of midwifery practice as evident within the profession’s philosophy. Findings suggest that the concept of midwives being ‘with woman’ is a dynamic and developing construct. The philosophy of being ‘with woman’ acts as an anchoring force to guide, inform and identify midwifery practice in the context of the rapidly changing modern maternity care landscapes. Gaps in knowledge and recommendations for further research are made.